Etyka a zarządzanie marketingowe – wybrane problemy - Winiarski, Marcin (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2015)
The aim of the article is the analysis of contemporary theoretical models of marketing and socio-economic factors influencing the marketing decision making consistent with the principles of law and ethics. The author points out that both: the definition of marketing proposed by the American Marketing Association 2007, as well as in the so-called holistic marketing model by Ph. Kotler, are contained clear recommendations indicating the need to respect the law and ethical rules of conduct on the market. In the article also raised was the issue of CRS and voluntary codes of conduct Code of Ethics and institutional arrangements within the framework of the legal system to support the ethical conduct of enterprises. However, according to the author opinion consumers due to modern communication devices and functioning of social media are and will be in the futuremajor factors in forcing decisions in accordance with ethics.
Keywords: etyka; zarządzanie marketingowe; orientacja holistyczna; promocja; media społecznościowe; CSR